Aplikasi Pemberian Dosis Pupuk Provasoli’s Enriched Seawater (PES) Yang Berbeda Pada Produksi Bibit Gracillaria verrucosa Melalui Kultur Jaringan Dengan Metode Propagasi Vegetatif - Rasnijal, Muhammad; Alauddin, Muhammad Hery Riyadi; Budiyati; Anton; Muhammad Syahrir; Yunarty; Saridu, Siti Aisyah; Wahid, Eriyanti; Regan, Yip; Hardianto, Toto; Supryady; Ihwan; Ernawati; Anwar; Mulato, Alwi; Sucipto; Syarief, Muhammad Nurman; Suleman, Yakub; Andini, Salsa; Suleman, Gabriella Augustine; Mulyono, Mugi; Anggoro, Agung Doni; Sektiana, Sinar Pagi; Achmad Suhermanto (Program Studi Budidaya Perairan, Fakultas Pertanian, Universitas Sriwijaya, 2025)
Cultivation of the seaweed Gracilaria verrucosa is necessary as a preventive measure against overexploitation. One applicable method is tissue culture, which requires special attention to nutrient needs to support accelerated growth. These nutrients can be provided through fertilization. One commonly used chemical fertilizer in seaweed tissue culture is Provasoli’s Enriched Seawater (PES). This study aims to determine the optimal PES fertilizer dosage for the production of G. verrucosa seedlings through tissue culture using a vegetative propagation method. This study used a completely randomized design with analysis of variance (ANOVA) consisting of four treatments of different PES fertilizer doses with three replicates for each treatment. The results showed that fertilizer dose variation did not significantly affect the absolute growth of explant weight, but tended to increase the number of growth points. Growth points began to increase in the second week for all treatments, and by the fourth week, the number of growth points at a 1.5% dosage showed a significant difference compared to other doses. The application of PES fertilizer in G. verrucosa seedling production through tissue culture with vegetative propagation indicates that different fertilizer doses do not affect explant growth but significantly influence the increase in growth points by the fourth week